The Effect of Social Media Marketing and e-WOM on Interest in Visiting Lon Beach - Lusy Rahmawati; Deykha Aguilika (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the influence of Social Media Marketing (SMM) and electronic word of mouth (e-WOM) on interest in visiting Lon Beach, Malang. The research sample consisted of 100 respondents determined using purposive sampling technique. Data were collected through a questionnaire measured using a Likert scale and analyzed using multiple linear regression with SPSS version 25. The results showed that SMM and e-WOM significantly influenced interest in visiting, both partially and simultaneously. The Adjusted R Square value of 0.617 indicates that 61.7% of the variation in interest in visiting can be explained by SMM and e-WOM, while the remaining 38.3% is influenced by other factors. The results of the hypothesis test show that SMM has a positive and significant influence on interest in visiting with a regression coefficient value of 0.496. Similar things were found in e-WOM with a coefficient value of 0.558. Simultaneously, these two variables have a mutually supportive relationship in increasing interest in visiting, as evidenced by the calculated F value of 80.603. This study confirms that effective social media marketing strategies and positive reviews from e-WOM can significantly increase public awareness and interest in visiting Lon Beach, Malang. These results provide important implications for tourism managers in designing digital-based marketing strategies.